MR metabolomics of fecal extracts applications in the study of bowel diseases - Bezabeh, Tedros (Magnetic resonance in chemistry : MRC, 2009)
NMR-based metabolomics is becoming a useful tool in the study of body fluids and has a strong potential to contribute to disease diagnosis. While applications on urine and serum have been the focus to date, there are a number of other body fluids that are readily available and could potentially be used for metabolomics-based disease diagnosis. One such body fluid is stool or fecal extract. Given its contact with and transient stay in the colon and rectum, stool carries a lot of useful information regarding the health/disease status of both the colon and the rectum. This could be particularly useful for the non-invasive diagnosis of colorectal cancer and inflammatory bowel disease--the two bowel diseases that are very common and pose significant public health problems. Different methodological considerations including the collection of sample, the storage of sample, the preparation of sample, NMR acquisition parameters, experimental conditions and data analysis methods are discussed. Results obtained in the detection of colorectal cancer and in the differentiation of the two major forms of inflammatory bowel disease (i.e. ulcerative colitis and Crohn's disease) are presented. This is concluded with a brief discussion on the future of MR metabolomics of fecal extracts